Design and Implementation of Encrypted Negative Password - Manasa, N; Preethi, P; Rakshitha, R; Jyothi, V; Lakshmikantha, S (International Journal of Computer Sciences and Engineering, 2025)
Secure password storage is the essential feature in system based on password verification, which is most broadly used verification technique, despite its some security weakness. In this paper, a password authentication scheme that is designed for secure password storage and could be easily consolidated into present authentication systems. In this framework the client enters the plain password which is hashed through the cryptographic hash function such as SHA-256. This hash function isthen converted into negative password. Finally using a symmetric-key algorithm such as Advanced Encryption Standard the negative password is encrypted into an ENP(Encrypted Negative Password).So this method makes it difficult for the intruder to crack the password. ENP method overcomes pre computation attacks.ENP does not provide extra elements such as salt which is one of useful advantage.ENP is the first password protection scheme which integrates cryptographic hash function, the negative password and the symmetric-key algorithm in a successful way.